‘El Ágora’: example of collaboration between university and public media - Calvo-Rubio, Luis Mauricio; Ufarte-Ruiz, María José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article details the work carried out within the teaching innovation project El Ágora, which is developed in the Faculty of Communication at the University of Castilla-La Mancha with the collaboration of the public broadcaster Radiotelevisión de Castilla-La Mancha. Every week, students produce a 30-minute radio programme which is broadcast on public radio. They also generate audiovisual content for other channels and platforms. Over three years (2019-), 168 students have participated in the project. Their evaluations are positive both on the acquisition of knowledge and on the experiential level.